Analisis Yuridis terhadap Peralihan dan Pendaftaran Hak atas Tanah Berdasarkan Putusan Pengadilan : Studi Putusan Nomor 268/Pdt.G/2022/PN.Lbp - Yulia Indah Pratiwi Nasution; hasim purba; Suprayitno (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The transfer of land rights should ideally be carried out through a Sale and Purchase Deed (AJB) before a Land Deed Official (PPAT), however in practice it is often based solely on a Binding Sale and Purchase Agreement (PJB), giving rise to disputes. This normative juridical research examines the legal force of a court decision as the basis for registering the transfer of land rights without an AJB. The results of the study indicate that a court decision that has obtained permanent legal force can substitute an AJB as the basis for registration. A PJB holds the position of a binding preliminary agreement and serves as evidence of a sale and purchase legal relationship. This is reflected in the Lubuk Pakam District Court Decision No. 268/Pdt.G/2022/PN.Lbp, which ordered the Land Office to process the transfer of rights based on the PJB and evidence of land possession.